2022
DOI: 10.15408/inprime.v4i2.25675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Underlying Distributions in The Accelerated Failure Time (AFT) Model on Mortality of Covid-19 Patients

Abstract: In 2022, the COVID-19 virus is still making headlines in various mass media because it is a virus that is very dangerous to health. The world health organization, WHO, explained that the virus caused a global pandemic that infected the whole world. The condition of a pandemic has not yet turned into an endemic. Based on the total confirmed COVID-19 positive cases, Indonesia ranks 18th in the world out of 222 infected countries. To determine the influence factors on COVID-19 cases, survival analysis is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, Jal-Usman et al [4] identified covariates associated with the recovery time of COVID-19 patients in Philippines using the AFT model. Likewise, Meiza et al [1] also determined the factors that significantly affect the mortality of Covid-19 patients in Indonesia using the AFT model.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jal-Usman et al [4] identified covariates associated with the recovery time of COVID-19 patients in Philippines using the AFT model. Likewise, Meiza et al [1] also determined the factors that significantly affect the mortality of Covid-19 patients in Indonesia using the AFT model.…”
Section: Introductionmentioning
confidence: 99%